Práticas avaliativas em docência compartilhada no 6º ano do Ensino Fundamental em uma escola da Rede Municipal de São Paulo - Santos, José Roberto dos (2020)
This investigation proposes elements for the analysis about the evaluative practices carried out in the contexto of teaching in the interdisciplinar cycle in shared teaching in matematics classes in a class of 6th grade of the Municipal System of São Paulo. The authors cited in the theoretical framework as: Léa Depresbiteris and Marialva Tavares (2009); Fernandes (2008, 2009, 2011, 2019); Peter Airasian and Michael Russel (2014), contributed to the understanding of the pedagogical uses of assessment for classroom learning and reflections on the process the development of pedagogical practice. As a general objective, we seek to identify and analyze the interactions established between the specialist teacher (PE) and the reseracher teacher (PP) in shared teaching. For its realization, the action research methodology was used ans inspired by the assumptions of Tripp (2005) and is fou phases (acting, describing, evaluating and planning) that met the researcher´s intentions, not only for data collection, but as a subject involved in the investigative action. In this sense, the paths for the preparation of three assessment instruments (objective test with multiple choice questions, rubric and pedagogical documentation) and the reflections and changes in atitudes expressed by the actors in the exercise of shared teaching are presented. The results presented allow us to say that this public Education of São Paulo between the years (2014-2019) contribuited effectively for the teachers to develop the pedagogical didatic work in a collaborative and reflective on evaluative practices, having diredt effects on the role os students and the improvement of their learning in the contexto of the investigate reality